INCREASING CHILDREN'S CREATIVITY THROUGH CONSTRUCTIVE PLAY WITH LEARNING MEDIA - Tomi Bidjai (International Journal of Teaching and Learning, 2025)
This research aims to explore the influence of constructive play with learning media on increasing children's creativity. Through a literature study, this research presents a comprehensive analysis of how constructive play activities can be an effective tool for developing children's creative abilities. Using a qualitative approach, this study collects and processes data from various sources such as journals, articles and books related to the topic. The research results show that constructive play with the support of appropriate learning media can create an environment that is conducive to the growth of children's creativity. This activity allows children to explore, experiment and discover through a fun learning process. It was also found that the role of educators in directing and providing various learning resources has a significant impact on the effectiveness of these activities. The conclusion of this research states that the application of constructive play as a learning method is an effective strategy for increasing children's creativity, as long as it is supported by the selection of appropriate learning media and positive interactions between children and educators. This research recommends further development in the practical application of constructive play with innovative learning media to support children's creative growth and development.